KEMAMPUAN REPRESENTASI MATEMATIS SISWA DALAM MEMECAHKAN SOAL BERBASIS HOTS DITINJAU GAYA BERPIKIR SEKUENSIAL DAN ACAK - Pratiwi Novitasari; Budi Usodo; Laila Fitriana (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This research aims to determine the mathematical representation ability of students with sequential and random thinking styles in solving HOTS-based mathematical problems. This type of research is a qualitative descriptive study. The instrument that used in this research is the main instrument (researcher) and supporting instrument (questionnaire, test, and interviews). The data collection was carried out by online due to the Covid-19 pandemic conditions which made it impossible to collect the data directly. The data analysis techniques of research are reduction data, presentation data, and drawing conclusions.. The subjects of this study were four students with CS, AS, CR, and AR thinking style. The results of research showed that students with a concrete sequential thinking style were able to meet the indicators of visual, symbolic, and verbal mathematical representation abilities. Students with an abstract sequential thinking style are able to meet the indicators of visual and verbal mathematical representations. Students with a concrete random thinking style are able to meet the indicators of visual, symbolic, and verbal mathematical representation abilities. Students with abstract random thinking style are only able to meet the indicators of visual mathematical representation ability in solving HOTS-based mathematical problems.